2020
DOI: 10.48550/arxiv.2012.01748
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A journey in ESN and LSTM visualisations on a language task

Alexandre Variengien,
Xavier Hinaut

Abstract: Echo States Networks (ESN) and Long-Short Term Memory networks (LSTM) are two popular architectures of Recurrent Neural Networks (RNN) to solve machine learning task involving sequential data. However, little have been done to compare their performances and their internal mechanisms on a common task. In this work, we trained ESNs and LSTMs on a Cross-Situationnal Learning (CSL) task. This task aims at modelling how infants learn language: they create associations between words and visual stimuli in order to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Ceni et al suggested an excitable network attractor method to explain the operational mechanism of ESNs in specific tasks [ 16 ]. Variengien et al proposed a recurrent state space visualization method, visualizing the learning process of ESNs, as well as revealing the effects of hyperparameters on reservoir dynamics [ 17 ]. Armentia et al tried to illustrate how perturbed features affected the readout of ESNs using a perturbation-based importance attribution method [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ceni et al suggested an excitable network attractor method to explain the operational mechanism of ESNs in specific tasks [ 16 ]. Variengien et al proposed a recurrent state space visualization method, visualizing the learning process of ESNs, as well as revealing the effects of hyperparameters on reservoir dynamics [ 17 ]. Armentia et al tried to illustrate how perturbed features affected the readout of ESNs using a perturbation-based importance attribution method [ 18 ].…”
Section: Introductionmentioning
confidence: 99%